OPTIMALISASI PENGGUNAAN ASAP CAIR DARI TEMPURUNG KELAPA SEBAGAI PENGAWET ALAMI PADA IKAN SEGAR - Sinar Abrina Anggraini; Susy Yuniningsih (Universitas Tribhuwana Tunggadewi Malang, 2017)
During this cooling fish handling is only done by fishermen because it is considered the most effective. But with the rise in fuel prices, the purchasing power of ice fishermen has become even more severe, so the need to find alternative ways of preserving fish that is inexpensive, easy to obtain and have a noticeable effect on the quality of fresh fish as well as safe for the preservation of fresh fish. Liquid smoke technology is an effective potential to help maintain the quality of fresh fish with coconut shell as raw materials. The purpose of this study was to obtain the optimum moisture content of the length of time drying the coconut shell into liquid smoke.This research used an experimental method with long time drying the coconut shell. This study begins with cleansing, enumeration, and drying coconut shell for 0 day, 1 day, 2 days, and 3 days. Then do the pyrolysis process until the process redestilasi and filtration column. Results of liquid smoke grade 3 and grade 1 was analyzed by GC-MS and LC-MS. Treatment on fresh fish is done using a variable length of time drying the coconut shell and the results conducted organoleptic tests include color, aroma, texture and taste.The result of this research is a long time optimal drying for 3 days, with a water content of 1.96%, 6.25% acid concentration, and pH value of 1.9. While the magnitude of the yield of 35.8% at 0 days